LOXL2 attenuates osteoarthritis through inactivating Integrin/FAK signaling - Caixia Zhang (Nature Portfolio, 2021)
Abstract Temporomandibular joint OA (TMJOA) is a common degenerative joint disease, leads to structural damage and ultimately loss of function. Matrix degradation is one of the first pathogenesis during the progression of OA, it was effective to inhibit matrix degradation to block the development of OA. In this study, an in vivo model (compressive mechanical force) and an in vitro model (IL-1β) were used to induce OA-like changes in TMJ cartilage and chondrocytes. We revealed lysyl oxidase like-2 (LOXL2) play a critical role in TMJOA. LOXL2 expression decreased in mechanical stress/IL-β induced TMJOA-like lesions in both in vivo models and in vitro models. Furthermore, recombinant LOXL2 (rhLOXL2) treatment ameliorated the degenerative changes induced by mechanical stress in vivo, including the thinning cartilage, down-expression of collagen II and proteoglycan, and over-expression of TNF-a, while LOXL2 antibody (anti-LOXL2) treatment exacerbated these changes. Mechanistically, the protection of LOXL2 in chondrocytes was induced partly through activation of the Integrin/FAK pathway. The inhibition of the Integrin/FAK pathway could neutralized the effects caused by rhLOXL2. Collectively, our study suggests that the LOXL2 plays a protective role in mechanical stress induced TMJOA-like changes, and the Integrin/FAK pathway may be a key downstream pathway in this process.